Efektivitas Kemampuan Menulis Paragraf Dengan Penggunaan Media Seri Kartun di Kelas III MIN 4 Tapin - Lailan Alfisyah; Tutus Rani Arifa; Jumiati J (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This type of research uses an experimental research method with a pretest-posttest control group design. This method is carried out by giving an initial test on the pretest-posttest before being given treatment to measure the initial conditions. Furthermore, the Posttest was given treatment and the Pretest was not given treatment. After completing the treatment, the Pretest and Posttest were given another test as the Posttest. Before the results of the study were analyzed with the t-test, the prerequisites were tested with normality and homogeneity tests. In testing the hypothesis using the t-test, obtained tcount = 3.57 and from the t distribution table obtained ttable = 1.68 with a = 5%. This shows that tcount > ttable. So tcount > ttable is accepted. This means that the average learning outcomes of Posttest students who are taught with Cartoon Series Media are significantly different from the average conventional learning outcomes. From the research results, the average posttest = 87.63 and the average pretest = 62.37. This means that the Cartoon Series Media is effective and improves student learning outcomes by 25.26.